2016
DOI: 10.3151/jact.14.706
|View full text |Cite
|
Sign up to set email alerts
|

Change in Relative Density of Natural Rock Minerals Due to Electron Irradiation

Abstract: We investigated changes in the density of natural rock minerals following high-energy electron irradiation, using the plasmon peak shift of electron energy-loss spectra and transmission electron microscopy. The target materials were the natural rock minerals α-quartz, orthoclase, anorthite, albite, biotite, muscovite, and chlorite. These crystalline minerals can be classified into three groups based on their Si-network geometries: 3-dimensional 6-member ring; 4-member ring + 6-member ring; and planar 6-member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…It is unclear why the dimensions of aggregates (except limestone) instead expanded. An expansion strain value of 4% for quartz has been reported in past research following electron irradiationinduced metamictization (Maruyama and Muto 2016), but the data obtained here did not reach this value. Taking into account the large variation and the little differ- Fig.…”
Section: (C) Aggregatescontrasting
confidence: 83%
See 2 more Smart Citations
“…It is unclear why the dimensions of aggregates (except limestone) instead expanded. An expansion strain value of 4% for quartz has been reported in past research following electron irradiationinduced metamictization (Maruyama and Muto 2016), but the data obtained here did not reach this value. Taking into account the large variation and the little differ- Fig.…”
Section: (C) Aggregatescontrasting
confidence: 83%
“…A recent study reported that quartz subject to 100-keV electrons expands by only 4%, which is markedly smaller than the 16-18% expansion caused by neutron irradiation. Thus, the mechanism of neutron metamictization is different from that of the electroninduced metamictization (Maruyama and Muto 2016).…”
Section: Concretementioning
confidence: 97%
See 1 more Smart Citation
“…When the sample's composition and chemical bonding character is almost constant, a lower energy position in the plasmon energy center can be understood as a lower density area in the sample, that is, less contact state. [ 34 ] Thus, it will be concluded that annealing at 300 °C provides superior contact without generating critical side reactions, leading to enhance the electrochemical active area and then reduce the R int .…”
Section: Resultsmentioning
confidence: 99%
“…The RIVE is related to many properties of the original rock like its mineral composition, grain size and orientation of minerals (Denisov et al 2012;Maruyama et al 2017;Le Pape et al 2020). For instance, it is well known that silicate-bearing aggregates develop higher RIVE compared to carbonate-bearing aggregates (Maruyama and Muto 2016;Le Pape et al 2018). Therefore, to assess the degradation risk of the biological shield, it is neces-sary to have the accurate mineralogy of aggregates and their properties in a such environment (Maruyama et al 2017;Le Pape et al 2020).…”
Section: Introductionmentioning
confidence: 99%